2014
DOI: 10.1021/ol4034868
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to the Heterocyclic Core of the Calyciphylline A and Daphnicyclidin A-Type Daphniphyllum Alkaloids via Tandem Cyclization of a Neutral Aminyl Radical

Abstract: A streamlined approach to the tertiary amine-containing core of the calyciphylline A and daphnicyclidin A-type Daphniphyllum alkaloids is presented. A known carvone derivative is converted into the core structure in only four synthetic operations, and it is well poised for further elaboration. The key enabling methodology is a radical cyclization cascade beginning with addition of a secondary, neutral aminyl radical to the β-position of an enone, followed by trapping with a pendant alkyne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…17 Findings that enones analogous to substrate 1 cyclized efficiently, while the corresponding allylic alcohol 14 led only to N–Cl reduction (R 2 N–Cl → R 2 N–H) were consistent with our hypothesis but were insufficient to provide insight into 5-exo and 6-exo cyclizations of conformationally unbiased substrates. Thus, we selected representative unactivated and activated olefin substituents to investigate under these conditions.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…17 Findings that enones analogous to substrate 1 cyclized efficiently, while the corresponding allylic alcohol 14 led only to N–Cl reduction (R 2 N–Cl → R 2 N–H) were consistent with our hypothesis but were insufficient to provide insight into 5-exo and 6-exo cyclizations of conformationally unbiased substrates. Thus, we selected representative unactivated and activated olefin substituents to investigate under these conditions.…”
supporting
confidence: 56%
“…We found that unactivated substrates 3a–3b 18 afforded good to excellent yields of cyclized products 4a–4b when treated with azobisisobutyronitrile (AIBN) and the weak H-atom donor ( i Pr) 3 SiH at 100°C in THF. 14,19 Bicyclic amine 4b was formed as a single diastereomer. The relative stereochemistry is consistent with previous stereochemical studies of 5- exo , 5- exo tandem cyclizations.…”
mentioning
confidence: 99%
“…The structural complexity and observed bioactivities of the Daphniphyllum alkaloids have inspired numerous efforts toward their synthesis. 4,5,6 …”
mentioning
confidence: 99%
“…4 This strategy utilized a neutral dialkyl aminyl radical 7 derived from chloroamine 2 to access tricyclic core 3 . 8 This cyclization was the first to employ a neutral aminyl radical in a cyclization with an enone, and represented one of two reported 6- exo cyclizations of aminyl radicals.…”
mentioning
confidence: 99%
See 1 more Smart Citation